Modulation of stretch activation influences the stretch‐shortening cycle effect in in vivo human knee extensors - Iseul Jo; Wolfgang Seiberl; Hae‐Dong Lee (Physiological Reports)
Abstract This study investigated the effects of progressively increasing voluntary activation during the stretch phase on force and work production in the stretch‐shortening cycle (SSC) of human knee extensors. Fifteen young adults performed SSCs under four stretch activation conditions: passive stretch (ST0%‐SC), feedback‐guided active stretch (ST40%‐SC and ST80%‐SC), and maximal effort stretch (ST100%‐SC). All conditions involved maximal voluntary activation during shortening, followed by a fixed‐end contraction at 20°. Outcome measures included joint torque and work, estimated fascicle force and work, vastus lateralis fascicle length and velocity, and quadriceps activation. Compared to passive stretch, active stretch conditions produced greater SSC effects, with no significant differences between ST80%‐SC and ST100%‐SC. Fascicle work did not differ significantly across conditions, suggesting a decoupling between joint‐level output and fascicle‐level contribution. Active stretch primarily enhanced force production during early shortening; however, the SSC effect persisted until mid‐to‐late shortening (80° to 38°) in ST80%‐SC. ST0%‐SC also showed nearly twice the fascicle shortening velocity of other conditions. Following shortening, ST100%‐SC exhibited greater residual force depression during the isometric phase, despite similar activation. These findings demonstrate that voluntary activation during stretch modulates SSC effect through a complex interplay involving muscle‐tendon unit decoupling and history‐dependent effects, fascicle dynamics, and tendon compliance.